2011
DOI: 10.5771/0949-6181-2011-2-111
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management and organisational culture in higher education institutions

Abstract: Social media offer many opportunities for organizations but present, at the same time, many challenges, too. Particular attention must be paid to the new patterns of behavior emerging in organizations. We argue that these patterns derive both from the technical characteristics of the virtual environment and also from specific social structural conditions currently emerging. By referring to two case studies, we want to highlight and discuss the implications of these current developments and their opportunities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 59 publications
1
41
1
2
Order By: Relevance
“…Fifth, the authors decided to use articles in which "knowledge sharing" and academics appeared in the title or abstract. This method was chosen to avoid selecting non-related papers, to extract the correct number of publications, and to restrict the search to a (Alhammad et al, 2009;Amayah, 2013;Cheng et al, 2009;Fullwood et al, 2013;Goh & Sandhu, 2013;Heydari et al, 2011;Howell & Annansingh, 2013;Jahani et al, 2011;Jolaee et al, 2014;Karahoca et al, 2011;Kim and Ju, 2008;Li et al, 2006;Nordin et al, 2012;Gomezelj et al, 2011;Ramachandran, 2013;Ramayah et al, 2014;Rowley, 2000;Sandhu, Jain, & Ahmad, 2011;Sharimllah et al, 2007;Siddique, 2011;Sohail & Daud, 2009;Nielsen & Cappelen, 2014). Additionally, the authors agree that a positive approach to knowledge management by HEIs would facilitate the transition to a knowledge-based economy, enhance knowledge sharing, improve educational programmes and consequently improve the overall performance of universities.…”
Section: Figure 1 Research Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, the authors decided to use articles in which "knowledge sharing" and academics appeared in the title or abstract. This method was chosen to avoid selecting non-related papers, to extract the correct number of publications, and to restrict the search to a (Alhammad et al, 2009;Amayah, 2013;Cheng et al, 2009;Fullwood et al, 2013;Goh & Sandhu, 2013;Heydari et al, 2011;Howell & Annansingh, 2013;Jahani et al, 2011;Jolaee et al, 2014;Karahoca et al, 2011;Kim and Ju, 2008;Li et al, 2006;Nordin et al, 2012;Gomezelj et al, 2011;Ramachandran, 2013;Ramayah et al, 2014;Rowley, 2000;Sandhu, Jain, & Ahmad, 2011;Sharimllah et al, 2007;Siddique, 2011;Sohail & Daud, 2009;Nielsen & Cappelen, 2014). Additionally, the authors agree that a positive approach to knowledge management by HEIs would facilitate the transition to a knowledge-based economy, enhance knowledge sharing, improve educational programmes and consequently improve the overall performance of universities.…”
Section: Figure 1 Research Designmentioning
confidence: 99%
“…Large numbers of articles were published in the Journal of Knowledge Management and the Journal of Knowledge Management and Practice, according toSerenko and Bontis (2009); these journals were among the highestranked KM publications. Discipline areas in these journals included management, human resources management, education management and technology, and information systems as depicted inFigure 2.5 Examining Knowledge Sharing in Higher Education Institutions (HEIs)Given knowledge is HEIs input as well as and output, they have maintained a unique and distinctive sittings compared to other organizations(Gomezelj et al, 2011); studies point out institutions are in the business of both generating and disseminating knowledge…”
mentioning
confidence: 99%
“…The trusting and collaborative culture illustrated in SEs can lead to greater willingness among SE members to share insights and expertise with each other in order to contribute to the successful performance of their organisation (Wang and Ahmed, 2003;Omerzel et al, 2011).…”
Section: Insert Figure 2 Herementioning
confidence: 99%
“…In the integration stage, the study found that there was no dissemination of knowledge transfer beyond the level of real estate program to the other units. Omerzel et al (2011) argues that one way to ensure the retention, documentation, and accessibility of knowledge beyond individual lecturers' knowledge base, is the development of a knowledge management system. The study found that this did not happen as part of the project where all knowledge transfer would be documented.…”
Section: Discussionmentioning
confidence: 99%